Influence of dentin conditioning with polyacrylic acid on the shear bond strength of a nano-filled resin-modified glass ionomer cement. - Zady J. Torres-Rivera; Juan Augusto Fernández-Tarazona; Alex Sandro de Souza (Universidad de Concepción., 2020)
Purpose: This in vitro study aimed to evaluate the influence of dentin conditioning with polyacrylic acid on the shear bond strength of the nano-filled resin-modified glass ionomer cement Ketac N100 (3MESPE). Material and methods: Eighteen bovine incisors were randomly divided into two groups (n=18): group 1, without dentin surface treatment, and group 2, with dentin surface treated with 10% polyacrylic acid for 15 seconds. In both groups the primer was applied before the application of the nano-filled resin-modified glass ionomer cement (Ketac N100) and light-cured for 20 seconds. After 24 hours, the specimens were submitted to thermocycling for 350 cycles, and the teeth were immersed in distilled water at room temperature. After 24 hours, specimens were tested for shear bond strength at 1mm/minute crosshead speed. The collected data were analyzed using the non-parametric test of Mann Whitney (p<0.05). Results: There was a significant difference in shear bond strength values between the treatment and control groups, the group with dentin conditioning with 10% polyacrylic acid showed higher shear strength values than the group without dentin treatment. Conclusion: Application of 10% polyacrylic acid on dentin increases the shear bond strength values of nano-filled resin-modified glass ionomer cement.